Analisis Penyebab Bottleneck dalam Produksi Lip Balm di PT Rumah Rumput Laut Menggunakan Diagram Fishbone - Zaqi Fathul Rohman; Shakkira Bintang Maharani; Triana Mega Oktarina; Sayyidah Dzakira Azra; Fatimah Zahra Rito; Ghina Yunita (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study aims to analyze the causes of bottlenecks in lip balm production at PT Rumah Rumput Laut by using a survey approach and fishbone diagram analysis method. The research method used is a descriptive method with survey approach which was conducted at PT Rumah Rumput Laut, Bogor Regency, West Java. Data were collected through observations and interviews with related parties in the production process based on previously identified problems. A fishbone diagram was used to identify the factors causing bottlenecks, which were grouped into six main categories, namely: manpower, machine, method, material, measurement, and environment. The results of the fishbone diagram analysis show that bottlenecks in lip balm production are caused by the irregular flow of material transfer, long waiting time for the quality control process, and limited production capacity. To overcome this problem, it is necessary to improve the operator supervision system, implement a regular machine maintenance schedule, rearrange the production space layout, and use technology to monitor machine conditions in real time.